Progressive Neurologic Dysfunction in a Psoriasis Patient Treated With Dimethyl Fumarate - Bartsch, Thorsten (Ann Neurol, 2015)
Progressive multifocal leukoencephalopathy (PML) has recently been described in psoriasis or multiple sclerosis patients treated with fumaric acid esters (fumarates), who had developed severe and long-standing lymphocytopenia (<500/mm(3)). We report a psoriasis patient who presented with progressive neurologic dysfunction and seizures after 2.5 years of fumarate therapy. Despite absolute lymphocyte counts remaining between 500–1000/mm(3), his CD4(+) and CD8(+) T-cell counts were markedly low. MRI showed right hemispheric and brainstem lesions and JC virus DNA was undetectable in his cerebrospinal fluid. Brain biopsy revealed typical features of PML as well as JC virus-infected neurons. Clinicians should consider PML in the differential diagnosis of fumarate-treated patients presenting with brain lesions or seizures even in the absence of severe lymphocytopenia.